2015
DOI: 10.1021/jacs.5b01374
|View full text |Cite
|
Sign up to set email alerts
|

The Tipper–Strominger Hypothesis and Triggering of Allostery in Penicillin-Binding Protein 2a of Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: The transpeptidases involved in the synthesis of the bacterial cell wall (also known as penicillin-binding proteins, PBPs) have evolved to bind the acyl-d-Ala-d-Ala segment of the stem peptide of the nascent peptidoglycan for the physiologically important crosslinking of the cell wall. The Tipper-Strominger hypothesis stipulates that β-lactam antibiotics mimic the acyl-d-Ala-d-Ala moiety of the stem, and thus are recognized by the PBPs with bactericidal consequences. We document that this mimicry exists also a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…In this regard, the Tipper-Strominger hypothesis [67], in other words, that β-lactam antibacterials mimic the conformation of the D-Ala-D-Ala component of the PBP bacterial cell wall substrate, may be relevant [68], in that in order to get to the stage where reaction to the acylenzyme complex can occur the β-lactam antibacterial must efficiently compete with the natural substrate for binding [69]. Following from biophysical evidence that some nucleophilic serine enzymes may bind their substrates in a high-energy conformation which strains the amide bond [70][71][72], a refinement of the Tipper-Strominger hypothesis suggests that (some) β-lactam antibacterials may mimic a strained conformation of the D-Ala-D-Ala entity (Figure 2) [73][74][75].…”
Section: Future Science Groupmentioning
confidence: 99%
“…In this regard, the Tipper-Strominger hypothesis [67], in other words, that β-lactam antibacterials mimic the conformation of the D-Ala-D-Ala component of the PBP bacterial cell wall substrate, may be relevant [68], in that in order to get to the stage where reaction to the acylenzyme complex can occur the β-lactam antibacterial must efficiently compete with the natural substrate for binding [69]. Following from biophysical evidence that some nucleophilic serine enzymes may bind their substrates in a high-energy conformation which strains the amide bond [70][71][72], a refinement of the Tipper-Strominger hypothesis suggests that (some) β-lactam antibacterials may mimic a strained conformation of the D-Ala-D-Ala entity (Figure 2) [73][74][75].…”
Section: Future Science Groupmentioning
confidence: 99%
“…While high-level ceftaroline resistance can be explained by mutations in the transpeptidase domain that alter the active site geometry, low-level resistance associated with mutations within the allosteric site was explained by a novel allosteric modulation of the active site [15, 1820]. Ceftaroline binds to the PBP2a allosteric site at therapeutic concentrations and triggers the opening and acylation of the active site by a second ceftaroline molecule [7, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Ceftaroline binds to the PBP2a allosteric site at therapeutic concentrations and triggers the opening and acylation of the active site by a second ceftaroline molecule [7, 20]. Mutations within the PBP2a allosteric domain alter the triggering mechanism and possibly affect protein–protein interactions needed for peptidoglycan biosynthesis [7, 14, 19, 2123].…”
Section: Introductionmentioning
confidence: 99%
“…New or improved mechanism of action; b. New physicochemical properties that makes it impossible for bacterial drug efflux pumps to recognize them and to remove them from bacterial cell; c. Ability to withstand the action of bacterial deactivating enzymes; d. Ability to bind to the modified target in bacteria [41][42][43][116][117][118][119].…”
Section: Resultsmentioning
confidence: 99%
“…Fishovitz et al reported that the triggering of the allosteric cite of PBP2 enzyme by one β-lactam antibiotic enables another β-lactam drug to interact with the active cite of that protein. Therefore, they report that there is synergy in the action of ceftaroline and some other β-lactams like oxacillin, imipenem, and meropenem against the MRSA bacterial strains [43].…”
Section: Fig 3 Penicillin G (A) and Cefaclor (B)mentioning
confidence: 99%